Increased body mass index is a risk factor for acute promyelocytic leukemia. Issue 1 (6th January 2021) - Kashanian, Sarah M.; Li, Andrew Y.; Mustafa Ali, Moaath; Sutherland, Mark E.; Duong, Vu H.; Hambley, Bryan C.; Zacholski, Kyle; El Chaer, Firas; Holtzman, Noa G.; Imran, Mohammad; Patzke, Ciera L.; Cornu, Jonathan; et al.
Abstract: Introduction: Obesity has become increasingly prevalent worldwide and is a risk factor for many malignancies. We studied the correlation between body mass index (BMI) and the incidence of acute promyelocytic leukemia (APL), non‐APL acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), and control hospitalized patients without leukemia in the same community. Methods: Multicenter, retrospective analysis of 71 196 patients: APL (n = 200), AML (n = 437), ALL (n = 103), nonleukemia hospitalized (n = 70 456) admitted to University of Maryland and Johns Hopkins Cancer Centers, and University of Maryland Medical Center. Results: Patients with APL had a significantly higher unadjusted mean and median BMI (32.5 and 30.3 kg/m 2 ) than those with AML (28.3 and 27.1 kg/m 2 ), ALL (29.3 and 27.7 kg/m 2 ), and others (29.3 and 27.7 kg/m 2 ) ( P < .001). Log‐transformed BMI multivariable models demonstrated that APL patients had a significantly higher adjusted mean BMI by 3.7 kg/m 2 ( P < .001) or approximately 10% ( P < .01) compared to the other groups, when controlled for sex, race, and age. Conclusions: This study confirms that when controlled for sex, age, and race there is an independent association of higher BMI among patients with APL compared to patients with ALL, AML, and hospitalized individuals without leukemia in the same community.